2019
DOI: 10.3389/fphar.2019.00028
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Modulate Somatostatin Receptors Expression and Synergize With the Somatostatin Analog Pasireotide in Prostate Cells

Abstract: Prostate cancer (PC) is one of the most frequently diagnosed cancers and a leading cause of cancer-related deaths in Western society. Current PC therapies prevalently target the functions of androgen receptor (AR) and may only be effective within short time periods, beyond which the majority of PC patients progress to castration-resistant PC (CRPC) and metastatic disease. The role of estradiol/estradiol receptor (ER) axis in prostate transformation and PC progression is well established. Further, considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…On the other hand, ERα-selective agonist PPT did not modify cell migration. Consistent with these results, study has shown that the activation of ERβ by DPN also promotes survival and migration of CPEC cell line, established from prostate cancer patients (19). Furthermore, the expression of ERβ5 (ERβ splice variant) in PC-3 cells increased the cell migration, and the expression of ERβ2 and ERβ5 increased the invasion, but did not change the proliferation of the cells (39).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, ERα-selective agonist PPT did not modify cell migration. Consistent with these results, study has shown that the activation of ERβ by DPN also promotes survival and migration of CPEC cell line, established from prostate cancer patients (19). Furthermore, the expression of ERβ5 (ERβ splice variant) in PC-3 cells increased the cell migration, and the expression of ERβ2 and ERβ5 increased the invasion, but did not change the proliferation of the cells (39).…”
Section: Discussionsupporting
confidence: 67%
“…The expression of estrogen receptors ERα and ERβ changes in different stages of the prostate cancer and conflicting findings on the roles of these receptors in the prostate cancer continue to emerge [reviewed by (11)(12)(13)(14)(15)]. However, studies have shown that ERβ may be potentially oncogenic in prostate cancer (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Parallel studies in TRAMP-FVB mice showed that a low-dose genistein diet (250 mg/kg) promoted PCa growth and metastasis compared to control and a high-dose genistein diet (1000 mg/kg), showing a biphasic effect of isoflavones on PCa [142]. Paller et al found that an increase in quercetin intake, another well-known isoflavone contained in capers, leads to a reduced risk of PCa, in African-Americans with vitamin D deficiency, while Sun et al showed that its use, associated with metformin, inhibits the growth, migration, and invasion on PC3 and LNCaP cells by inhibiting the VEGF/AKT/PI3K signaling pathway [143,144]. Similarly, fisetin has been suggested to act as a dual inhibitor on PI3K/AKT and mTOR metabolic pathways in PCa cell lines.…”
Section: Polyphenolsmentioning
confidence: 99%
“…In this sense, certain components of the somatostatin system, especially somatostatin-receptors (SST 1-5 , encoded by the somatostatin receptor 1-5 genes (SSTR1-5)), are expressed in both normal and tumor prostate tissues, where they may play a relevant role in the development and progression of this disease [6][7][8][9]. Specifically, some components of this system (e.g., SST 1 and SST 2 ) can contribute to reduce different tumor parameters, including cell proliferation and migration, whereas other components [i.e., the truncated splicing variant of SST 5 with four transmembrane domains (SST 5 TMD4 variant)] promote aggressiveness features of PCa [10][11][12].…”
Section: Introductionmentioning
confidence: 99%